Periodic Limb Movements during Sleep: A New Sleep-Related Cardiovascular Risk Factor? - Alessandria, Maria; PROVINI, FEDERICA (Frontiers in Neurology, 2013)
In recent years, a growing body of evidence suggests that periodic limb movements during sleep (PLMS) are associated with hypertension, cardiovascular and cerebrovascular risk. However, several non-mutually exclusive mechanisms may determine a higher cardiovascular risk in patients with PLMS and the link between the two remains controversial. Prospective data are scant and the temporal relationship between PLMS and acute vascular events is difficult to ascertain because although PLMS may lead to acute vascular events such as stroke, stroke may also give rise to PLMS. This article describes the clinical and polygraphic features of PLMS and examines the literature evidence linking PLMS with an increased risk for the development and progression of cardiovascular diseases, discussing the possible pathways of this association.